2009
DOI: 10.3109/10903120903349838
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Low-Energy Versus High-Energy Biphasic Defibrillation Shocks Following Prolonged Ventricular Fibrillation

Abstract: Introduction-Since the initial development of the defibrillator, there has been concern that, while delivery of a large electric shock would stop fibrillation, it would also cause damage to the heart. This concern has been raised again with the development of the biphasic defibrillator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…36,80 -81 In a recent prolonged cardiac arrest pig study, however, biphasic 360 J shocks did not appear to cause more cardiac damage than biphasic 150 J shocks (LOE 5). 82 Human studies involving BTE waveforms 74,83 with energy levels up to 360 J have not shown harm as indicated by biomarker levels, ECG findings, and ejection fractions.…”
Section: Myocardial Damage Associated With Higher-energy Levelmentioning
confidence: 99%
“…36,80 -81 In a recent prolonged cardiac arrest pig study, however, biphasic 360 J shocks did not appear to cause more cardiac damage than biphasic 150 J shocks (LOE 5). 82 Human studies involving BTE waveforms 74,83 with energy levels up to 360 J have not shown harm as indicated by biomarker levels, ECG findings, and ejection fractions.…”
Section: Myocardial Damage Associated With Higher-energy Levelmentioning
confidence: 99%
“…Initiating defibrillation either at 150 J or at 200 J biphasic waveform energy does not result in any significant difference in outcomes for first-shock effect. An animal study comparing first shock of 150 J versus 360 J showed no difference in ROSC rates 16. A randomized comparison of fixed lower (150 J) versus escalating HE (beginning at 200 J) levels for defibrillation in out-of-hospital cardiac arrest (BIPHASIC Trial.…”
Section: Discussionmentioning
confidence: 99%
“…Wide variations were reported in VF termination rates using LE biphasic shocks 1315. Very few laboratory trials have been conducted to determine whether fixed LE or escalating HE protocols would provide the best chances for successful defibrillation 16,17. An out-of-hospital study demonstrated potential for good survival with escalating HE shocks 18.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged spontaneous or induced ventricular fibrillation, compared to short episodes, required a greater potential gradient for successful defibrillation and to achieve this gradient there was need of higher shock energy (Niemann et al, 2010). After 6 minutes of ventricular www.intechopen.com fibrillation, the first shock defibrillated the heart in 82% of the cases with 360 Joules biphasic shocks and only in 25% of the cases with 150 Joules biphasic shocks (Walcott et al, 2010). There are several clinical conditions, which require higher than usual energy for successful defibrillation: hypertrophic cardiomyopathy, acute ischemia, and several antiarrhythmic agents.…”
Section: Studies Of the Defibrillation Thresholdmentioning
confidence: 99%